Cardiovascular responses of physically active colligate subjects during normal and warm conditions, and determination of sweat rates - Asim Cengız; Bade Tekbas; Bilal Demırhan (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to determine the effects of elevated climate temperature on the exercise-induced physiological responses and fluid need in physically active subjects. Ten physically active colligate subjects (age: 22.79 ± 4.98 yrs) participated in a counter balanced cross over design that consisted of performing a cycling run (65% VO2 max) for 30 min under normal and condition of wearing multiple layers of clothes, separated by 7 days. Measures of heart rate, body temperature, and rating of perceived exertion (RPE) were obtained at 10-min intervals (0, 10, 20, and 30 min) from the onset of exercise.  Sweat rates, and amount of fluid needed to replace water loss during exercise were calculated. Heart rate, body temperature, and RPE increased all the way to the end of the exercise for both conditions but more in warm conditions. These findings point out that sports facilitators should take the athletes' physiological responses in training in warm dry weather seriously, guide athletes to rehydrate with adequate amount of water.